Peran Pengelola Perpustakaan dalam Menumbuhkan Budaya Gemar Membaca Siswa Tunarungu di Perpustakaan SLB-B Pangudi Luhur Jakarta - Yusdi Yanti; Ida Farida (Librarianship in Muslim Societies, 2022)
The decline in reading culture in school students is an issue that comes to the fore today. The government and schools have made various efforts to develop a reading culture. Many roles should be involved so that the student is in an environment that always encourages him to read hard. Library managers are an essential part of having a role in fostering a culture of reading. This study aims to determine the role and constraints of library managers in motivating the reading interest of deaf students in the library of SLB-B Pangudi Luhur a Jakarta. This study aims to determine library managers' roles and constraints in motivating the reading interest of deaf students. This research is descriptive with a qualitative approach and the case study method. Data collection techniques are carried out through interviews and literature reviews. Using B. F. Skinner's Operant Conditioning Learning Theory, research shows that library managers play their role in motivating deaf students' reading interest through mandatory library programs. The activities carried out by library managers in the program include storytelling, using picture books, composing for students to imagine, and collaborating with teachers. Library managers carry out these activities to encourage deaf students to read, especially when there are obstacles in the process of absorbing their ear language and difficulties in generating emotions such as anxiety, fear, anger, depression, and low communication resulting in a lack of self-confidence. Obstacles experienced by library managers in motivating students include the lack of adequate human resources and the lack of availability of new books. The manager of the SLB-B Pangudi Luhur Jakarta Library applies the oral/aural verbal communication method in communicating to support and make it easier to motivate the reading interest of deaf students.